Nursing care of a patient with postoperative pain of mixed hemorrhoids treated by Traditional Chinese Medicine fumigation (中药熏蒸技术治疗1例混合痔术后疼痛患者的护理体会) - WEI Yongchun (魏永春); QIN Shasha (秦沙沙); E Haiyan (鄂海燕); TANG Ling (唐玲); DONG Yuxia (董玉霞); WANG Yali (王亚丽) (中西医结合护理)
This paper reviewed the nursing measures of Traditional Chinese medicine fumigation in a patient with pain and edema after operation of mixed hemorrhoids. Under the guidance of dialectical nursing theory of traditional Chinese medicine, the fumigation technology of Traditional Chinese medicine granules was adopted. After treatment, the pain of patients was significantly reduced and the edema was significantly improved. (本文总结1例混合痔术后伴疼痛及水肿的患者行中药熏蒸技术治疗的护理经验, 包括中药熏蒸的药方组成、操作方法、注意事项以及饮食、生活等常规护理, 在中医辨证施护理论指导下, 采取针对性措施, 患者疼痛和水肿症状明显改善。)